Measuring hospital qualities. A preliminary investigation on Health Impact Assessment possibilities for evaluating complex buildings - Brambilla, Andrea; Buffoli, Maddalena; Capolongo, Stefano (Acta Biomedica Atenei Parmensis, 2019)
Background and aim of the work: World Health Organization states that is possible evaluating projects’ qualities via Health Impact Assessment (HIA) but there are not specific HIA tools on hospital buildings assessment. Researchers show significant relationships between built environment and health. The research purpose is investigating how existing tools for healthcare building assessment are encouraging the development of possible hospital HIA evaluation. Methods: Based on previous works, 13 assessment tools have been included and a comparison of the criteria has been conducted to understand which the most prevalent topics are. The tools have been analyzed through literature, technical manuals and official websites. The authors identified 12 thematic categories where criteria from different tools have been clustered and discussed. Results: The most prevalent criteria are related to Indoor Environmental Quality (IEQ) (20%). In the oldest tools the evaluation was mainly on technical features while in recent instruments several indicators are related to Architectural features and innovation (48%), Education (23%) and Food (11%). Conclusions: There is growing interest in tools capable of addressing healthy hospitals encouraging IEQ, physical activity and healthy food provision related to occupants’ health outcomes. This preliminary study set the basis for further development on hospital facility HIA tools.